A Study on Contamination of Nitrite in Edible Bird's Nest (Swiftlets) - M. F., Ismail; N. A., Sabri; Saiful Nizam, Tajuddin (2014)
Edible bird's nest (EBN) derived from the hardened saliva of swallows and considered as high-end health food with organic nutrients. Excessive of nitrite were found in EBN imported from Malaysia to China in past few years and still an issue today. Therefore the purpose of this study is to investigate the source of EBN contamination. EBN were collected in Aspa Cottage, Kuantan and divide into two treatment (a) treated EBN (tEBN), which exposed to bird soil; (b) untreated EBN (uEBN). The nitrite (NO2) and nitrate (NO3) level were analyzed using ion chromatography for 14 days. Result showed the level of NO2 and NO3 level for treated EBN reported significantly more than untreated EBN. The source of NO2 and NO3 could have been derived mainly from the bird soil. It is suspected also the color of EBN change from yellowish and brownish simultaneously as level of NO2 and NO3 of EBN increased. Thus the bird soil could be the source of the NO2 contamination in EBN.